Recoverable, Record-High Lactic Acidosis in a Patient with Glycogen Storage Disease Type 1: A Mixed Type A and Type B Lactate Disorder - Yonatan Oster; Isaiah D. Wexler; Samuel N. Heyman; Elchanan Fried (Case Reports in Medicine)
A 17-year-old patient with GSD type 1a (von Gierke disease) was hospitalized with an extremely elevated serum lactate following an intercurrent infection and interruption of his frequent intake of carbohydrates. The patient developed shock, oliguric renal failure, and cardiorespiratory failure requiring mechanical ventilation and inotropes. At the peak of metabolic decompensation and clinical instability, serum lactate reached a level of 47.6 mmol/L which was accompanied by a severe anion gap metabolic acidosis with a pH of 6.8 and bicarbonate of 4 meq/L. The patient was stabilized with massive infusions of sodium bicarbonate (45 meq/h) and glucose and recovered without the need for dialysis. This patient illustrates pathophysiologic mechanisms involved in the development of extreme mixed type A and type B lactic acidemia, reflecting altered metabolic pathways in GSD type 1, combined with tissue hypoperfusion. The rationale for the specific interventions in this case is outlined.